Research on the Impact of Blending Dissociated Methanol Gas on the Performance and Emissions of Marine Medium-Speed Methanol Engines - Xiaoyu Liu; Jie Zhu; Zhongcheng Wang; Zihan Wang; Zihao Zhao; Wenhua Wang; Haiping Cai (Journal of Marine Science and Engineering)
This study conducts a detailed analysis of the mixed combustion of dissociated methanol gas (DMG) and methanol in a marine medium-speed methanol engine through numerical simulation methods. The research focuses on the impact of partially replacing methanol with DMG on engine combustion characteristics and emissions under both stoichiometric and lean-burn conditions. Employing the MAN L23/30H diesel engine as the experimental model, direct injection of DMG is achieved by installing gas injectors on the cylinder head. Utilizing the CONVERGE software, we simulate the injection and combustion processes of methanol and DMG and subsequently analyze the effects of varying DMG blending ratios on in-cylinder pressure, heat release rate, mean chamber temperature, as well as NOx, HC, CO, and soot emissions. The research findings indicate that, under stoichiometric combustion conditions at both rated and idle speeds, the incorporation of DMG leads to increases in the peak in-cylinder pressure, peak heat release rate, and peak in-cylinder temperature, with these peaks occurring earlier. Additionally, it is observed that emissions of HC, CO, and soot are reduced. Under lean combustion conditions at rated speed, in the absence of DMG blending, increasing the excess air ratio results in an initial increase followed by a decrease in both fuel-indicated and overall-indicated thermal efficiency. However, with the blending of DMG, these efficiencies improve as the excess air ratio increases. Notably, the highest efficiencies are achieved when the excess air ratio is 1.8 and the blending ratio of DMG is 30%.